2000
DOI: 10.1038/sj.cgt.7700127
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell proliferation in HCC-9204 hepatoma cells by a c-myc specific ribozyme

Abstract: A ribozyme (RZ) gene targeting c-myc mRNA was synthesized and cloned. Cleavage reaction showed that cleavage of the RZ was efficient and specific. The RZ gene-containing retrovirus vector pDOR-RZ was transfected into HCC-9204 hepatoma cells, which constitutively express high levels of c-myc using Lipofectamine. Positively transfected cells were selected using G418. In situ hybridization showed that both pDOR-RZ and pDOR vectors had been integrated into the chromosome of HCC-9204 cells. Dot blot hybridization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The reduction of hOGG1 mRNA and protein level in A549-R cell line by our ribozyme was 61.5% and 55.1%, respectively. Because the hammer head ribozyme gene knockdown technique usually can reduce the expression of a specific gene by 30-90% in somatic cells depending on the gene and cell type [Leopold et al, 1995;Wiechen et al, 1998;Cheng et al, 2000;Funato et al, 2000;Kamochi et al, 2002], this indicates that our hOGG1 knockdown efficiency was comparable with that from the other studies. The MTT assay can reflect the activity of succinate dehydrogenase.…”
Section: Discussionsupporting
confidence: 66%
“…The reduction of hOGG1 mRNA and protein level in A549-R cell line by our ribozyme was 61.5% and 55.1%, respectively. Because the hammer head ribozyme gene knockdown technique usually can reduce the expression of a specific gene by 30-90% in somatic cells depending on the gene and cell type [Leopold et al, 1995;Wiechen et al, 1998;Cheng et al, 2000;Funato et al, 2000;Kamochi et al, 2002], this indicates that our hOGG1 knockdown efficiency was comparable with that from the other studies. The MTT assay can reflect the activity of succinate dehydrogenase.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have shown that c-myc is barely expressed in normal liver tissue (Voravud et al, 1989). By contrast, c-myc has been found overexpressed in most of the hepatoma cell lines and its repression by ribozyme or antisense therapy induces differentiation and growth inhibition of these cells (Farshid and Tabor, 1992;Ebinuma et al, 1999;Cheng et al, 2000). Also, in vivo studies have shown that c-myc expression may gradually increase from normal liver to chronic hepatitis, cirrhosis and HCC (Himeno et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…C-myc is frequently over-expressed in tumors with poor prognosis. The ribozyme-mediated down-regulation of myc was recently shown to be very effective in tumors displaying high myc levels and high proliferating activity [Cheng J. et al (2000)]. …”
Section: Neoplastic Pathologiesmentioning
confidence: 99%